Integrity of Damage Control Posterior Spinal Fusion Constructs for Patients With Polytrauma: A Biomechanical Investigation. Issue 23 (December 2015) - Pekmezci, Murat; Herfat, Safa; Theologis, Alexander A.; Viscogliosi, Paul; Demirkiran, Gokhan; McClellan, R. Trigg; Ames, Christopher
Abstract : Study Design: Biomechanical. Objective: Evaluate spinal stability achieved with different levels of posterior percutaneous fixation (postPerc) for thoracolumbar fractures in cadavers subjected to ICU activities. Summary of Background Data: "Spine damage control" involves postPerc performed within 24 hours of injury and staged, elective, definitive stabilization. Amount of instrumentation needed to initially achieve adequate spinal stability, minimize morbidity, and accommodate ICU care needs between stages are not defined. Methods: In full-unembalmed cadavers motion-tracking sensors were placed at T11 and L1. A T12 corpectomy with PLC injury was stabilized with 1, 2, and 3 levels of PostPerc above/below the injury. Motions between T11 and L1 were measured during Log-Roll and Sit-Up on an ICU bed. After in situ testing, anatomic spinal motion ranges were determined under pure moment loads. Results: 5 cadavers were evaluated. For Log-Roll, 2 and 3 levels above/below restored stability to intact, whereas 1 level above/below did not for axial rotation. For translation, all instrumentation restored stability to intact. During Sit-Up, a linear increase in flexion was observed. At 45° Sit-Up, 2 and 3 levels above/below were similar to intact for flexion; 1 level above/below had significantly more flexion. All instrumentations restored translation to intact for Sit-Up; significantly more axial collapse occurred for instrumentation compared with intact. During ex situ testing, 2 and 3 levels above/below were similar; 1 level above/below had significantly greater laxity in flexion, extension, and axial rotation. Conclusion: Posterior instrumentation 2 or 3 levels above/below a severe thoracolumbar fracture model can restore spinal stability back to its intact condition. 2 levels of fixation above/below this "worst-case scenario" is minimum fixation sufficient to provide absolute spinal stability in the ICU setting as a "Damage Control" technique in patients with polytrauma. In less severe injury models, 1 level of fixation above/below may provide adequate spinal stability; although this should be confirmed in future investigations. Level of Evidence: N/A